Augmentation in photocurrent through organic ionic plastic crystals as an efficient redox mediator for solid-state mesoscopic photovoltaic devices. Issue 5 (15th February 2021) - Sonigara, Keval K.; Vaghasiya, Jayraj V.; Prasad, Jyoti; Machhi, Hiren K.; Ansari, Mohammad Shaad; Qureshi, Mohammad; Soni, Saurabh S.
Abstract : Photoresponsive organic ionic plastic crystals redox mediators, namely OIPC-I/OIPC-Br contributing photocurrent from the phenoxazine moiety to augment the efficiency of SK4 sensitizer by ∼40% compared to conventional electrolyte. Abstract : Mesoscopic photovoltaic devices (MPDs) are significantly promising for sustainable light-harvesting through solid-state compact designs. Materials with multifunctional properties play a vital role in improving the processability, stability, and cost of such devices. Here, a single-route synthesized sensitizer and multifunctional organic ionic plastic crystals (OIPCs) are introduced, and OIPCs are employed as a redox couple and light-harvesting contributor as a binary sensitizer-electrolyte system enabled via energy transfer in a photovoltaic device. Materials OIPC-I, OIPC-Br, and SK4 sensitizer possess a typical N -alkyl-phenoxazine (POZ)– N -alkyl-benzimidazole (BM)-type architecture, and OIPCs hold additional iodide and bromide anions at the quaternary nitrogen of BM. OIPCs show redox potential generated from anions corresponding to I − /I3 − and Br − /Br3 − as well as suitable molecular energy levels due to the POZ–BM donor–acceptor pathway, which results in a self-regenerative photovoltaic response in FTO/ p -TiO2 /OIPC/Pt configuration without any sensitizer. The SK4 sensitizer has suitable energy levels below the redox potential level of OIPCs, which are well regenerated by OIPCs during the photo-electricity generation in the photovoltaic device. Here, an OIPC–Br-based device with high photovoltage (0.98 (±0.02) V) and pronounced photocurrent from extra electrons gained through the POZ donor present in OIPC by the energy transfer mechanism shows 45% energy transfer towards the dye or TiO2 . The OIPC-I based device demonstrated 43% (±3) higher efficiency compared to the conventional benzimidazolium-based electrolyte due to improved photocurrent and photovoltage. Single component OIPC-I based solid-state MPD devices show excellent ∼95% stability up to 5000 h, which is more than the OIPC–Br based device.